Comprensión Newtoniana de la caída de cuerpos. Un estudio de su evolución en el Bachillerato - Acevedo Díaz, José Antonio (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this paper we show the various interpretations of the fall of solid bodies under different situations given by Spanish High School students and stress the need for a Conceptual Change through the methodological and attitudinal change from a constructivist outlook upon learning. We also put forward some considerations on the results obtained with respect to the pupils' sex difference and the fact that they had chosen scientific or humanistic studies.